Regionalisme Arsitektur Melayu Pada Kantor DPRD Langkat - Rahma Wardani Siregar (JAUR (JOURNAL OF ARCHITECTURE AND URBANISM RESEARCH), 2022)
Regionalism in architecture is an attempt to show back into the regional architecture style into the present building. North Sumatera is one multiethnic provinces with indigenous Malay. Malay native tribes in North Sumatra is one of the eastern coastal area in the district of Langkat. Currently in Langkat district with many buildings designed to redisplay the regional characteristics as Langkat Parliament's office which can be seen in the use of architectural elements of the past  is a Langkat’s Malay architecture. The method used in this research is descriptive qualitative to see firsthand the Langkat Parliament's office. Results of the analysis conducted with the purpose of knowing the architectural elements that affect Langkat Parliament's office as regionalism architecture. There are some architectural elements that affect regionalism in the Parliament office.